PENGARUH HASIL SURVEI TENTANG ELEKTABILITAS CAPRES-CAWAPRES 2014 TERHADAP PERILAKU PEMILIH DI SURABAYA - Kurniawan, Dista (Jurnal Review Politik, 2015)
This article discusses the effect of public perception toward the survey results on the president and vice president candidate’s electability and its relation to the voters’ behavior in Surabaya during the 2014 presidential election. There has been a presupposition which assumes that the people’s perception toward the survey results on the president and vice president candidate’s electability would likely influence the behavior of the electors. Using quantitative approach, the results of the study indicate that the influence of people’s perception on the survey results about the president and vice president candidate’s electability is “low”. It is about 0.291. Furthermore, determination test with the value of 0.085 means that 8.5% variables of voting behavior are influenced by the public perception toward the survey results, and the remaining 91.5% are influenced by other factors.